2000
DOI: 10.1039/b000748j
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt minimisation in willemite (CoxZn2−xSiO4) ceramic pigments

Abstract: Industrially available blue ceramic pigments, with the exception of vanadium-zircon blue, (Zr,V)SiO 4 , contain Co. To minimise the use of toxic and scarce cobalt, while also maintaining an intense blue colour, the performance as blue ceramic pigments of both Co 2+ -Zn 2 SiO 4 (willemite) and Zn 2+ -Co 2 SiO 4 (olivine) solid solutions was studied. The addition of cobalt in the willemite lattice was minimised. A wide range of compositions, Co x Zn 22x SiO 4 (x = 2, 1.95, 1.5, 1, 0.9, 0.5, 0.05 and 0), were pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(57 citation statements)
references
References 5 publications
2
54
0
1
Order By: Relevance
“…In fact, to counter the high toxicity of cobalt compounds, intense blue pigments with less important amounts of cobalt (non-stoichiometric) were reported to have been recently manufactured under the form of Co-containing host minerals such as gahnite (ZnAl 2 O 4 ). [27] Gazulla et al [34] report that no less than a minimum of 40% Zn in weight is necessary for obtaining and detecting by XRD the mixed spinel form ZnCoAl 2 O 4 , whereas other studies reported that no difference is observed in the XRD pattern of ZnO in Co-doped ZnO minerals, even up to 12% Co addition. [18,35,36] As a matter of fact, while the XRD technique confirmed its limitation in distinguishing between Co/Al and Co/Al/Zn spinel pigments, the Raman spectra acquired on these pigments clearly showed additional features in the Zn-containing spinels and hence make the mineralogical identification and differentiation of these two kinds of pigments from now on possible.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…In fact, to counter the high toxicity of cobalt compounds, intense blue pigments with less important amounts of cobalt (non-stoichiometric) were reported to have been recently manufactured under the form of Co-containing host minerals such as gahnite (ZnAl 2 O 4 ). [27] Gazulla et al [34] report that no less than a minimum of 40% Zn in weight is necessary for obtaining and detecting by XRD the mixed spinel form ZnCoAl 2 O 4 , whereas other studies reported that no difference is observed in the XRD pattern of ZnO in Co-doped ZnO minerals, even up to 12% Co addition. [18,35,36] As a matter of fact, while the XRD technique confirmed its limitation in distinguishing between Co/Al and Co/Al/Zn spinel pigments, the Raman spectra acquired on these pigments clearly showed additional features in the Zn-containing spinels and hence make the mineralogical identification and differentiation of these two kinds of pigments from now on possible.…”
Section: Resultsmentioning
confidence: 98%
“…In addition, the range of hues available for Co-spinels is much more diverse than for olivines. [27] The spinel-like mineral has a cubic structure (isometric), which may be expressed with the stoichiometry AB 2 O 4 consisting of a packed oxygen arrangement in which the cations reside in the octahedral and tetrahedral sites. A represents a divalent metal ion such as Co II , Mg II , Fe II , Ni II , Mn II or Zn II , whereas B represents trivalent metal ions such as Co III , Al III , Fe III , Cr III , Mn III or Ti III .…”
Section: Problemsmentioning
confidence: 99%
“…For example, Calbo et al minimised the Cr content and partially substituted Ni by Mg and Zn in the spinel type black pigment Ni(Fe, Cr) 2 O 4 [4]. Fores et al obtained the pigment Co 0.05 Zn 1.95 SiO 4 with an intense blue colour, which contains only 2.5% mol of cobalt [5]. Furthermore, Munoz et al minimised the amount of Cr in the green pigment formulation Cr 1.14 Al 0.86 O 3 [6].…”
Section: \ 1 Introductionmentioning
confidence: 98%
“…CIE chromaticity diagram ( Figure 7 and [20] Whereas a number of Co II oxides in tetrahedral coordination are known (for example spinel CoAl 2 O 4 , and Zn 1-x Co x Al 2 O 4 , [28] willemite Co x Zn 2-x SiO 4 , [29] Co 2 SnO 4 , [30] and Co-doped ZnO [31] ), which are blue in colour (except the latter, which is green), very few Ni II oxides in tetrahedral coordination are known: Ni-doped β-Al 2 O 3 , [20] Ni-doped hibonite (CaAl 12 O 19 ) [32] and BaZn 2-x Ni xSi 2 O 7 , [20] to our knowledge, displaying green, turquoise, and red colours.…”
Section: Colour and Optical Characterisationmentioning
confidence: 99%